A crítica entre a literatura e a História: o percurso da crítica literária de Sérgio Buarque de Holanda dos verdes anos à profissionalização do ofício - Mariana Thiengo (2011)
This thesis aims to present a profile of Sergio Buarque de Holanda as a literary critic, emcompassing his writings from the period between 1920 to 1950, approximately. It highlights his integration in the intellectual field of his time and his participation in debates and contentions of the Modernism. In this way, the study attempts to understand the way Sérgio Buarque, in the dispersal of his early writings and their readings, had dealt with the notion of the gradual formation of feelings, from his writing debut. He tried to adapt such notion to his understanding of the avant-garde, in particularly the Expressionism and the Surrealism, starting to use, on a recurring basis, in his heroic phase of the Modernism, the term "expression", surely related to the notion alluded. Amongst the many novelties that he unfolds in the modern literature, including incorporating its tensions in his language, Sérgio Buarque focused more thoroughly on the poetry of Manuel Bandeira, where he identified a sui generis combination of originality and melancholy, elements that, without a doubt, in the poetry of Bandeira, include the best you could desire in terms of modern poetry, which represents, unlike other artistic events, an art marked by the nation, as argued by Gottfried Benn. In the poetry of Manuel Bandeira, in 1922, Sérgio Buarque, still writing in the brisk pace of his discoveries, glimpsed a journey which would take him from the subjectivity, shaped into artistic expression, to the slow and gradual formation of the feelings that would consolidate the nation. This, so to speak, is the axis around which moves this study and it focus on the debates and controversies that Sérgio Buarque starred (this is the term) in the 1920s and covers the writings of literary criticism of the 1940s, when such a romantic sight reveals not only on a fresh assessment to the poetry of Manuel Bandeira, but also a very particular way with which Sérgio Buarque reads and evaluates the fictional production of the period, choosing the psychological or intimist novel in the countercurrent of regionalist paradigm of that time.